Candi Panataran: Candi Kerajaan Masa Majapahit. - Hariani Santiko (KALPATARU, 2012)
Candi Panataran adalah candi kerajaan (State Temple) Kerajaan Majapahit, didirikan di sebuah tanah yang berpotensi sakral karena di tempat itu terdapat prasasti Palah dari jaman Kadiri, berisi tentang pemujaan Bhatara ri Palah. Berdasarkan angka tahun yang ditemukan di kompleks candi, setidaknya Candi Panataran dipakai sejak pemerintahan Raja Jayanagara hingga Ratu Suhita. Pada jaman Majapahit, Candi Panataran adalah candi untuk memuja Paramasiwa yang disebut dengan berbagai nama, tattwa tertinggi dalam agama Siwasiddhanta. Bahkan ada kemungkinan sebuah Kadewaguruan (tempat pendidikan agama) dibangun di sekitar kompleks candi, tetapi dimana kepastian letaknya, belum jelas. Candi Panataran adalah “pusat spiritual” kerajaan Majapahit. Abstract. Panataran Temple was a state temple of the Majapahit Kingdom, which was built on a piece of land that had the potency to be sacred because there was an inscription, the Palah inscription, from the Kadiri period. The inscription is about devotion to Bhatara ri Palah. Based on a date found within the temple complex, it is assumed that at least the Panataran Temple was functioned since the reigning periods of King Jayanagara until Queen Suhita. During the Majapahit period, the Panataran Temple was a temple dedicated to Paramasiwa, who was known by various names, the highest tattwa in Siwasiddhanta religion. In fact, there is a possibility that a Kadewaguruan (centre of religious teachings) was built around the temple complex, but the exact location is yet to be found. The Panataran Temple was the “spiritual centre” of the Majapahit Kingdom.